(untitled) (Research, Society and Development, 2020)
The present study aims to describe, from the narratives of pioneer masters, how they organized themselves to regulate the sport in Brazil. Therefore, the following questions were elaborated: How was the process of creating and developing the first associations and federations to regulate the sport in the country? After the appearance of these regulatory entities, what was done to improve the technical level of Brazilian athletes and masters? In an attempt to answer such questions, hybrid oral history was used as a methodology. It was possible to conclude that the institutionalization process started in 1983, in partnership with the Brazilian Confederation of Boxing. Soon after, the first state federations were created. Thai Boxing (Muay Thai) was recognized as a sport by the National Sports Council in 1988, after undergoing a restructuring. After institutionalization, it was possible to hold international seminars and exchanges for the sport to get closer to what is practiced in Thailand and other countries. Successful initiative, so much so that Brazil currently ranks among the top five countries in the world, with world champions in different categories.